L'impact Des Normes Alimentaires Traditionnelles Sur Les Conseils Nutritionnels Chez Les Gestantes Ébrié Akouai De Côte d'Ivoire - Coulibaly, Mathieu Hermann (European Scientific Journal, ESJ, 2017)
Nutritional counseling disseminated by biomedicine during prenatal consultations is of particular importance in the context of reproductive health. These advices are given to the pregnant woman in order to prevent all forms of food imbalances that could harm her as well as the fetus. This is why it is essential for pregnant women to take this into account. But at the Ébrié akouai in Bingerville, pregnant women must also respect traditional food norms. The existence of this traditional diet is not without effects on nutritional counseling. These effects are manifold and result in noncompliance with nutritional recommendations. At the same time, they show the limits of the nutrition education of pregnant. We have tried to discover them through individual conversations, focus group and direct observations.